RESEPSI TERHADAP RAGAM METODE TAHFIZ ALQURAN: Studi Living Alquran Di Pondok Pesantren Assalafie Dan Assalafiat Babakan Ciwaringin Cirebon - Iis Sa’idatul Ulfah; Didi Junaedi (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2019)
Appreciation and respect the community of Muslims to holy so extraordinary. Addition to reading is Muslims memorize Al-Qur’an. Memorize Al-Qur'an do with various method. Many method found who can help and already easy in memorize it. Such as memorize methods at Assalafie and Assalafiat Islamic Boarding Schools. Thus in Islamic boarding schools there are memorize method of Al-Qur’an ILHAM. However, the students who memorize Al-Qur'an with various method, there are applied method classic, ILHAM and combination between classic and ILHAM. The reception students on various memorizing methods is so unique that it is positive, active and innovative. The reception students that uses the classic method of memorizing is feeling comfortable, easy and often repeating. The response of the ILHAM method almost all said it was fun, not saturated, as if playing games. Reception of the combined method is extraordinary, memorizing positions can be anywhere and anytime and easier to memorize.